The Effect of Business Strategy and Audit Quality on Real Earnings Management Moderated By Managerial Ownership - Purnamayani, Anak Agung Kompiang Ari; Musmini, Lucy Sri; Atmadja , Anantawikrama Tungga (Dinasti Publisher, 2025)
The research conducted on this occasion aims to determine the influence of defender business strategy, prospector business strategy and audit quality on real earnings management by using managerial ownership as a moderator. This research was conducted on infrastructure sector companies listed on the IDX in 2019-2023. This research is supported by population data of 62 companies using observations over a period of 5 years. In the process of facilitating sample data collection, a purposive sampling technique was implemented, so that data was obtained from 15 companies whose conditions had met the criteria for sampling with a period of 5 years of observation, where the sample data used was also obtained as many as 75 samples. The data used in this research is in the form of secondary data whose acquisition process is carried out online by analyzing using the Eviews version 12 application. The results of this research successfully found that defender and prospector business strategies do not affect real earnings management, audit quality has a significant positive effect on real earnings management, and managerial ownership is able to strengthen the influence of defender business strategies on real earnings management but does not yet have the ability to moderate the influence of prospector business strategies and audit quality on real earnings management. The contribution of this research can provide information on real earnings management through business strategy and audit quality moderated by managerial ownership so that investors and policy makers can monitor and reassess efforts to reduce real earnings management.